Early detection monitoring image of bearing fault thermal image in induction motor - Ghazali, K. H.; Khatun, Sabira; Mohamed Abdelaziz, Izzeldin Ibrahim; Jadin, Mohd Shawal; Karim, Rohana Abdul
AC Squirrel cage induction motors are the most important alternating current (ac) machine in industries due to their advantages of reliability, rugged construction, easy maintenance, and cost-effective pricing. More than 90% of all motors used in industry worldwide are ac induction motors (M.Peltola, 2002). Based on studies, the most common fault occurrences of induction motor are relate on bearing faults (Albrecht, Appiarius, McCoy, Owen, & Sharma, 1986; "IEEE Recommended Practice for the Design of Reliable Industrial and Commercial Power Systems," 1988; Thomson & Fenger, 2001). Yet, (Hashemian, 2011; Nandi, Toliyat, & Li, 2005; Schoen, Habetler, Kamran, & Bartfield, 1995) have identified that, up to 40%-50% of machinery defects are related to bearing faults. This has reveals that bearings are the primary cause and most severe and common fault in the motor system.